Seroprevalence of Hepatitis A in Children Followed-up with the Diagnosis of Chronic Hepatitis B Infection - Deveci, Ugur; Acar, Ufuk (Galenos Publ House, 2020)
Objectives: To investigate the seroprevalence of hepatitis A virus (HAV) infection in children with chronic hepatitis B virus (HBV) infection and to immunize patients who did not have anti-HAV immunoglobulin (Ig) G level in protective titer. Materials and Methods: A retrospective analysis was made in 79 children with chronic HBV infection between January 2017 and December 2018. Results: Of the patients with a mean age of 11.5 +/- 4.6 years (1-18 years), 64.6% were boys and 35.4% were girls (male/female=51/28). Anti-HAV (Ig) G was positive in 72.2% (n=57) of the cases. According to gender, the rate of sero-positivity was found to be 72.5% (n=37) in boys and 71.4% (n=20) in girls. HAV immunization was determined at the lowest rate (8.1%) in the 14-18 years age group. Although 3 patients vaccinated against HAV were anti HAV-IgG negative, and 39 patients who were not vaccinated were anti-HAV IgG positive. Conclusion: The seroprevalence of HAV should also be evaluated in children with chronic HBV infection. Morbidity and mortality due to HAV infection can be prevented by vaccinating non-immune patients.
Kronik hepatit B enfeksiyonu nedeniyle takip edilen çocuklarda hepatit A seroprevalansı
Keywords: Chronic hepatitis B infection; hepatitis A virus; super infection; seroprevalence; child